The effect of polymorphism at the serotonin transporter gene on decision-making, memory and executive function in ecstasy users and controls - Roiser, Jonathan P. (2006)
RATIONALE: 3, 4-Methylenedioxymethamphetamine (MDMA or “ecstasy”) is a popular drug of abuse known to result in depletions of the serotonin (5-HT) system. A number of studies have reported that ecstasy users differ from controls on a variety of measures of cognitive function. However, the literature is not consistent and many negative findings were also reported. One reason for such inconsistency might be interindividual variance in vulnerability to the deleterious effects of ecstasy due to a number of factors, both genetic and environmental. OBJECTIVES: To investigate the hypothesis that carriers of the s allele at the 5-HT transporter gene-linked polymorphic region (5-HTTLPR), which was associated with reduced serotonergic neurotransmission relative to the l allele, would be most vulnerable to the effects of ecstasy on cognitive function. METHODS: We assessed memory, decision-making, and executive function in ecstasy users and controls, stratifying by genotype at the 5-HTTLPR. RESULTS: We observed that the 5-HTTLPR genotype groups differed on a number of measures in both the ecstasy users and the controls. While performing a risky decision-making task, ss and ls controls attended to differences in the probability of winning chosen gambles to a greater extent than the ll controls. However, this difference was dramatically attenuated in the ss ecstasy users. Furthermore, independent of ecstasy use, volunteers of the ss genotype outperformed the ll genotype on a visual planning task. CONCLUSIONS: The results are consistent with the hypothesis that cognitive impairment in ecstasy users may depend on genetic variation at the 5-HTTLPR.